Use of fruits and seeds from Amazonian inundated forests in feeding trials with Colossoma macropomum (Cuvier, 1818) (Pisces, Characidae) - Roubach, Rodrigo; Saint-Paul, Ulrich (Journal of Applied Ichthyology, 1994)
With the annual floods fish are able to move into the inundated forests and procure fruits and seeds. Feedin trials with young Colossoma macropomum (Characidae) weighing 18 g were carried out to study keir efficiency to metabolize abundant fruits and seeds (Pseudobombax munuba, Oryza sp., Hevea spp., and Cecropia latiloba) from inundated forests. Crude rotein content of the fruits varied between 4.1 and 21.3%. Growth rates of fish were comared wit! those fed a control diet of 35% crude protein. The highest weight increases (2.5% per day) were obtained with the control diet. Within the fruit and seed treatment growth rates were correlated with the protein content of the food source; however, rotein efficiency ratio decreased. Best specific growth rate of 1.3% per day was obtained when feeding, P. munguba seeds (21.3% crude protein). With the treatments with P. munguba and Oryza sp. crude fat content of the fish body increased while the protein content decreased. As foodplain forests are of importance by nourishing many commercial fish species, negative consequences of floodplain deforestation for lsh communities are discussed. Copyright © 1994, Wiley Blackwell. All rights reserved